Criminal Action of Spreading Fake News - Tri Julita (Budapest International Research and Critics University, 2022)
The rise of the crime of spreading false news in the last two years has increased sharply. The data released by the Directorate of Cyber Crime for handling cases of spreading notifications and/or fake news has increased sharply. The crime of spreading false and misleading news is also contained in Article 390 of the Criminal Code, only in that article there is the phrase